Assessment of the effect of climate change on the floods in Bulgaria - Velichkova Rositsa (E3S Web of Conferences, 2020)
Global warming intensifies the water cycle. The intensified water cycle is considered to be among the reasons for the increment of floods in several regions on Earth. The floods and the ensuing disaster situations, which have increased over the past year, have caused massive material damage and economic losses to the Bulgarian population. The occurrence of floods was directly associated with the amount of rainfall in a given period. Therefore, the present study aims to assess the trends in rainfall changes in Bulgaria and their correlation with the floods over 8 years: from 2010 to 2017.